REV7 is essential for DNA damage tolerance via two REV3L binding sites in mammalian DNA polymerase ζ - Tomida, Junya (Nucleic Acids Res, 2015)
DNA polymerase zeta (pol ζ) is exceptionally important for controlling mutagenesis and genetic instability. REV3L comprises the catalytic subunit, while REV7 (MAD2L2) is considered an accessory subunit. However, it has not been established that the role of REV7 in DNA damage tolerance is necessarily connected with mammalian pol ζ, and there is accumulating evidence that REV7 and REV3L have independent functions. Analysis of pol ζ has been hampered by difficulties in expression of REV3L in mammalian cells, and lack of a functional complementation system. Here, we report that REV7 interacts with full-length REV3L in vivo and we identify a new conserved REV7 interaction site in human REV3L (residues 1993–2003), distinct from the known binding site (residues 1877–1887). Mutation of both REV7-binding sites eliminates the REV3L–REV7 interaction. In vivo complementation shows that both REV7-binding sites in REV3L are necessary for preventing spontaneous chromosome breaks and conferring resistance to UV radiation and cisplatin. This demonstrates a damage-specific function of REV7 in pol ζ, in contrast to the distinct roles of REV3L and REV7 in primary cell viability and embryogenesis.